Genome-wide identification and expression analysis of glutathione S-transferase gene family to reveal their role in cold stress response in cucumber - Xiaoyu Duan; Xuejing Yu; Yidan Wang; Wei Fu; Ruifang Cao; Lu Yang; Xueling Ye (Frontiers in Genetics, 2022)
The plant glutathione S-transferases (GSTs) are versatile proteins encoded by several genes and play vital roles in responding to various physiological processes. Members of plant GSTs have been identified in several species, but few studies on cucumber (Cucumis sativus L.) have been reported. In this study, we identified 46 GST genes, which were divided into 11 classes. Chromosomal location and genome mapping revealed that cucumber GSTs (CsGSTs) were unevenly distributed in seven chromosomes, and the syntenic regions differed in each chromosome. The conserved motifs and gene structure of CsGSTs were analyzed using MEME and GSDS 2.0 online tools, respectively. Transcriptome and RT-qPCR analysis revealed that most CsGST members responded to cold stress. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses for differentially expressed CsGSTs under cold stress revealed that these genes responded to cold stress probably through “glutathione metabolism.” Finally, we screened seven candidates that may be involved in cold stress using Venn analysis, and their promoters were analyzed using PlantCARE and New PLACE tools to predict the factors regulating these genes. Antioxidant enzyme activities were increased under cold stress conditions, which conferred tolerance against cold stress. Our study illustrates the characteristics and functions of CsGST genes, especially in responding to cold stress in cucumber.